Stakeholders' conceptualization of offshore aquaculture and small-scale fisheries interactions using a Bayesian approach - Ramos, Jorge (2019)
Recent coastal planning measures in south-east Portugal (Algarve), where offshore aquaculture developments were set up in fishing areas aiming to maximize expected utility of seafood production activities, raised some discontentment. Public policies created to safeguard offshore aquaculture (OSA) producers and limit small-scale fishing (SSF) activities must be adjusted accordingly in order to maximize income and keep discontentment at a minimum. We collected primary data from stakeholders, fishers (n = 18) and offshore aquaculture operators (n = 3) through participatory workshops and interviews by eliciting problematic issues derived from the offshore area creation and their relative relevance. We used these data to populate conditional probability tables and construct a related influence diagram (Bayesian belief networks) to model the affected system. We selected nine scenarios based on navigability and aquaculture area size with the aim of finding the best expected utility combinations for the OSA SSF system. The inferred results show that maximizing employment and keep pollution at low levels were the most influential factors to keep the system at a satisfactory level. The best decision was not to enlarge the aquaculture area, but to condition the access to other operational stakeholders, namely SSF operators from nearby areas. The overall results of the Bayesian belief network can be used to recommend coastal planners and decision-makers to deal with the interaction between OSA and SSF activities.(c) 2017 Elsevier Ltd. All rights reserved.